1987
DOI: 10.2334/josnusd1959.29.241
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of the outer enamel epithelium in the cervical loop of the rat incisor.

Abstract: IntroductionThere have been only a few morphological studies on the cervical loop (CL) of the enamel organ. It was originally reported on the basis of light microscopic observations that the CL of the rat incisor was difficult to discriminate into the four cell layers, i.e., the inner enamel epithelium, the stellate reticulum, the stratum intermedium and the outer enamel epithelium [1]. Later, however, it was shown by WARSHAWSKY et al. [2] that in the CL of the rat incisor, both the inner and outer enamel epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In IEE/OEE clusters, GO terms were mostly enriched in cell division and cell cycle, in agreement with their high proliferation activity ( Figure 2E ). In SI/SR clusters, GO enrichment indicated that they act as regulators of nutrient and ion transport ( Figure 2F ), in line with previous reports ( Kallenbach, 1978 ; Inage et al, 1987 ; Yoshida et al, 1989 ; Nakamura and Ozawa, 1997 ).…”
Section: Resultssupporting
confidence: 91%
“…In IEE/OEE clusters, GO terms were mostly enriched in cell division and cell cycle, in agreement with their high proliferation activity ( Figure 2E ). In SI/SR clusters, GO enrichment indicated that they act as regulators of nutrient and ion transport ( Figure 2F ), in line with previous reports ( Kallenbach, 1978 ; Inage et al, 1987 ; Yoshida et al, 1989 ; Nakamura and Ozawa, 1997 ).…”
Section: Resultssupporting
confidence: 91%